Kyrgyz Republic : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper reviews economic developments in the Kyrgyz Republic during 1990-95. From October 1993 onward, the authorities vigorously pursued restrictive credit policies, which led to monthly inflation rates falling from more than 30 percent in September and October 1993 to low single-digit levels from the spring of 1994 onward. In early 1994, all of the structural measures contemplated under the 1993 program were implemented. In May 1994, the government formulated a comprehensive medium-term economic program (1994-97) to stabilize further the economy and accelerate its structural transformation.